The role of L1 typology and L2 proficiency in null subject transfer - Smallwood, J (2021)
This dissertation is a large-scale investigation on the omission of subject pronouns by learners of null-subject languages. A null-subject language is one where pronouns are either optional or unnecessary to make reference to a primary subject. In these languages, (which includes, Spanish, Italian, Arabic, Mandarin Chinese, Russian, Swahili, and many others) dropping a pronoun does not result in ambiguity. However, English is a non-null-subject language and a subject pronoun is always required in referring expressions. The aim of the present study is to determine if this difference in subject parameters means that learners are more prone to omit pronouns in second language (L2) English production. The first research question of the present study asks, ‘do null subjects in the L1 transfer to L2 English?’ This question becomes more complex when we consider that there are more than one type of nullsubject language. How null subjects are licensed is in ‘canonical’ null-subject languages like Spanish is quite different from ‘radical’ null subject languages like Japanese. Typological classification, then, becomes an additional consideration and the basis of research question two. The literature has suggested, however, that regardless of L1, the effects of language transfer are still persistent at advanced levels of L2 proficiency. This means, that learners are still omitting pronouns in L2 English—beyond the B2 level—just as they would in their nullsubject first language (L1). Research question three queries whether proficiency, rather than L1, is the key factor in accurate L2 grammatical production.